1997
DOI: 10.1212/wnl.49.6.1655
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pyruvate dehydrogenase deficiency treated with ketogenic diets

Abstract: Inborn errors of the pyruvate dehydrogenase complex (PDC) are associated with lactic acidosis, neuroanatomic defects, developmental delay, and early death. PDC deficiency is a clinically heterogeneous disorder, with most mutations located in the coding region of the X-linked alpha subunit of the first catalytic component, pyruvate dehydrogenase (E1). Treatment of E1 deficiency hs included cofactor replacement, activation of PDC with dichloroacetate, and ketogenic diets. In this report, we describe the outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
145
1
10

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(157 citation statements)
references
References 12 publications
1
145
1
10
Order By: Relevance
“…It leads to decreased blood lactate and pyruvate concentrations and provides an alternative source of energy in the form of ketones (Wexler et al 1997) and has been shown to be helpful in reducing childhood onset epilepsy and paroxysmal dystonia (Barnerias et al 2010). However, its efficacy has been variable (Weber et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It leads to decreased blood lactate and pyruvate concentrations and provides an alternative source of energy in the form of ketones (Wexler et al 1997) and has been shown to be helpful in reducing childhood onset epilepsy and paroxysmal dystonia (Barnerias et al 2010). However, its efficacy has been variable (Weber et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…There are no proven treatments for PDH complex deficiency. Anecdotal studies have reported beneficial effects from the use of high-fat, ketogenic diets, which provide an alternative energy source to carbohydrate [7] and dichloroacetate (DCA), which inhibits PDH kinase and maintains E1α in its unphosphorylated, catalytically active form [8]. Neither intervention has been rigorously evaluated as a treatment for PDH deficiency in a controlled clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…Current treatments for PDH deficiency, which include the activation of residual PDH with dichloroacetate (6), the administration of cofactors (lipoic acid and thiamine) (7,8), and the provision of ketogenic diets (9,10), have yielded only limited or variable success (see Fig. 1).…”
mentioning
confidence: 99%
“…1). The technical challenges of working with small numbers of human patients has made it difficult to include all of the necessary controls and to systematically evaluate therapeutic agents and diets with varying proportions of calories from fat, carbohydrate, and protein (9,11). Furthermore, preexisting neurological disorders compound the difficulty of evaluating treatments.…”
mentioning
confidence: 99%